Protein Extraction from Spirulina Platensis with The Cellulase Enzyme Assistance - Le Nguyen Doan, Duy; Phan The, Duy; Le, Thi Thanh Hoa; Nguyen, Thi Xuan Quynh; Nguyen, Dang Ninh (Journal of Technical Education Science, 2022)
Microalgae is a relatively new, sustainable source of protein supplements. Among various microalgae strains, Spirulina platensis has shown an effective protein potential source compared with others. A high-performance protein recovery technology is required for this prospect. When the cellulase enzyme supported the recovery process, the condition to get the highest protein recovery efficiency (40.13±2.87%) were 50 UI/g dry algae for enzyme activity, 1:20 for the ratio of dry algae: solvent, 7.0 for pH value with a process temperature of 50oC for 90 minutes. This study succeeded in using cellulase enzymes to support protein extraction with high recovery efficiency from Spirulina platensis grown in Vietnam, opening up an additional source of protein in the trend of plant-based meat production.